Norms in the Field: Super Garuda Shield, Discursive Socialization, and the Construction of Indo-Pacific Security Identity (2007–2025) - Ilham Dary Athallah; Hayara Khairia; Tsabita Husna; Ronna Rihadatul Arsy; Bhintank Mi’thori Danial Firdaus (International Journal of Geography, Social, and Multicultural Education, 2026)
The annual Super Garuda Shield exercises have developed from a U.S.–Indonesia bilateral engagement into a recurrent multinational event that, by the mid-2020s, convened thousands of personnel and a widening circle of participating and observing states across multiple domains of training. Official communications surrounding the exercises repeatedly frame cooperation in terms of sovereignty, interoperability, partnership, and a “free and open Indo-Pacific,” positioning Super Garuda Shield as a productive site for examining how security cooperation is narrated as a norm-governed community rather than merely an instrument of capability building. It employs a longitudinal qualitative discourse analysis grounded in social constructivism, supplemented by the norm life cycle model and security community theory. The analysis identifies three empirical trajectories: a shift from bilateral to group-referential identity language across exercise iterations; the stabilization of interoperability as an uncontested procedural norm; and the progressive routinization of 'free and open Indo-Pacific' framing from advocacy toward taken-for-granted vocabulary, consistent with (Finnemore and Sikkink 1998)'s cascade and internalization stages. The discussion argues that repeated exercise participation functions as a socialization mechanism that generates “thin” but politically consequential expectations of cooperative security accounting for participation patterns and rhetorical convergence that neorealist and institutionalist frameworks leave underdetermined (USINDOPACOM 2025).